OPTIMALISASI PERAN SATUAN POLISI PAMONG PRAJA DALAM PENEGAKAN PERDA BULELENG NOMOR 6 TAHUN 2009 TENTANG KETERTIBAN UMUM TERHADAP PEDAGANG KAKI LIMA DI KABUPATEN BULELENG - Ricky Simarmata; Ratna Artha Windari; Dewa Bagus Sanjaya; Kusuma, Putu Riski Ananda (Jurnal Ilmu Hukum Sui Generis, 2024)
The purpose of this research is to (1) determine and evaluate the responsibilities and authority of Satpol PP in enforcing Buleleng Regional Regulation Number 6 of 2009 concerning Public Order, especially with regard to street vendors in Buleleng Regency. (2) To find out and study obstacles and problems in implementing Regional Regulation Number 6 of 2009 concerning Public Order, especially regarding street vendors in Buleleng Regency. This research uses empirical legal research with descriptive-analytical research characteristics with primary and secondary data types. The results of this research show that (1) the duties and authority of Satpol PP refer to Government Regulation No. 16 of 2018 concerning Civil Service Police Units. In its operations, the Buleleng Regency Satpol PP carries out guidance, supervision and action against street vendors who violate Buleleng Regional Regulation Number 6 of 2009. (2) enforcement of the Buleleng Regional Regulation carried out by the Satpol against street vendors in Buleleng Regency is not yet optimal because there are still obstacles, namely the enforcement factor. The law is where there is a lack of Satpol PP members who are PPNS, the factor of infrastructure supporting law enforcement, as well as the community factor (PKL) in Buleleng Regency which is lacking in awareness of the law itself. To overcome these obstacles, efforts that can be made include providing strict sanctions against street vendors who continuously violate Buleleng Regional Regulation Number 6 of 2009, increasing the resources and professionalism of the Satpol PP's performance, increasing coordination from each related sub-district agency and operations. routinely, and carry out regular preventive and coaching measures considering the low level of public awareness (PKL) in order to create order and cleanliness.